Rights to Restitution of Victims of Criminal Actions According to Article 7 Section (1) Law Number 13 of 2006 Junction Law 31 of 2014 Concerning the Protection of Witnesses and Victims - Hotma P Sibuea; Indra Lorenly Nainggolan; Jantarda Mauli Hutagalung (Budapest International Research and Critics University, 2022)
Several research problems that need to be answered are as follows. First, can the granting of victims' restitution rights based on Article 7A paragraph 1 (one) of Law Number 31 of 2014 be carried out by the aims and objectives of the legal principle of